Financial Literacy and Investment Decision in Nepalese Share Market - Pradhan, Barsha (Campion Journal of Multidisciplinary Research and Explorer, 2025)
This study investigates the role of financial literacy in shaping investment decisions in Nepal’s share market, focusing on the growing influence of financial literacy as Nepal’s stock market expands. The primary objectives were to explore the factors affecting investment decisions, analyze the relationship between these factors and financial literacy, and assess their impact on decision-making in Nepal’s share market. A survey of 470 investors from Kathmandu Valley was conducted, collecting data through structured questionnaires. Regression analysis was used to evaluate the impact of financial knowledge and financial behaviors on investment decisions. The findings suggest that financial literacy significantly improves investors' ability to make informed choices, reducing investment risks and enhancing portfolio performance. The research highlights that financial knowledge contributes to better decision-making and market understanding, with more literate investors showing increased confidence in managing their investments. Additionally, the research found that while financial behavior is crucial, its influence on decision-making is more complex, with some correlations showing negative effects, particularly in managing market risks. This study underscores the importance of enhancing financial literacy to support informed investment decisions and foster a more stable and efficient market environment.